Impact of the -1T>C single-nucleotide polymorphism of the CD40 gene on the development of endothelial dysfunction in a pro-diabetic microenvironment - Joshi, Pooja; Rehberg, Franziska; Rumig, Cordula; Kliemank, Elisabeth; Krenning, Guido; Kopf, Stefan; Hecker, Markus; Wagner, Andreas H. (Atherosclerosis, 2024)
BACKGROUND AND AIMS: Hyperglycemia reinforces pro-inflammatory conditions that enhance CD40 expression in endothelial cells (EC). Thymine to cytosine transition (-1T > C) in the promoter of the CD40 gene (rs1883832) further increases the abundance of CD40 protein on the EC surface. This study examines potential associations of the -1T > C SNP of the CD40 gene with type 1 (T1D) or type 2 (T2D) diabetes. Moreover, it investigates the impact of a pro-inflammatory diabetic microenvironment on gene expression in human cultured umbilical vein EC (HUVEC) derived from CC- vs. TT-genotype donors. - METHODS: Tetra-ARMS-PCR was used to compare genotype distribution in 252 patients with diabetes. Soluble CD40 ligand (sCD40L) and soluble CD40 receptor (sCD40) plasma levels were monitored using ELISA. RNA-sequencing was performed with sCD40L-stimulated CC- and TT-genotype HUVEC. Quantitative PCR, Western blot, multiplex-sandwich ELISA array, and immunocytochemistry were used to analyse changes in gene expression in these cells. - RESULTS: Homozygosity for the C-allele was associated with a significant 4.3-fold higher odds of developing T2D as compared to individuals homozygous for the T-allele. Inflammation and endothelial-to-mesenchymal transition (EndMT) driving genes were upregulated in CC-genotype but downregulated in TT-genotype HUVEC when exposed to sCD40L. Expression of EndMT markers significantly increased while that of endothelial markers decreased in HUVEC following exposure to hyperglycemia, tumour necrosis factor-α and sCD40L. - CONCLUSIONS: The -1T > C SNP of the CD40 gene is a risk factor for T2D. Depending on the genotype, it differentially affects gene expression in human cultured EC. CC-genotype HUVEC adopt a pro-inflammatory and intermediate EndMT-like phenotype in a pro-diabetic microenvironment.
Online verfügbar 14. November 2023, Version des Artikels 12. Juni 2024
Gesehen am 10.01.2025